Evaluasi Fungsi Kepemimpinan Dalam Meningkatkan Mutu Pembelajaran Sekolah Dasar Di Bengkulu - Abd. Rahman Rabbani; Khairiah Khairiah (Al-Khair Journal : Management, Education, and Law, 2022)
Abstract: The quality of learning in primary schools has created difficulties in the Leadership environment because some leaders have functioned professionally and others have difficulties in their professional functions. This study aims to evaluate the function of leadership in improving the quality of learning in elementary schools in Bengkulu. The research method used is descriptive qualitative. Sources of information in this study, using various sources, online media or print media. Such as books, and scientific articles, which exist nationally or internationally related to the function of leadership in improving the quality of learning in elementary schools. The results of the evaluation carried out show that the leadership function largely determines the quality of learning in elementary schools. Teachers as leaders in the classroom also greatly determine the quality of learning. So that researchers can suggest, if you want to improve the quality of learning in elementary schools, then increase the evaluation of leadership functions in elementary schools in Bengkulu.Keywords: Evaluation, Leadership function, Quality of Learning, Elementary SchoolÂ Abstrak: Mutu pembelajaran di sekolah dasar telah menciptakan kesulitan di lingkungan Kepemimpinan, dikarenakan sebahagian kepemimpinan telah berfungsi secara professional dan sebahagian yang lain mengalami kesulitan dalam fungsi keprofesionalannya. Tujuan dari penelitian ini untuk mengevaluasi fungsi kepemimpinan dalam meningkatkan mutu pembelajaran di sekolah dasar di Bengkulu. Metode penelitian yang digunakan adalah kualitatif deskriptif. Sumber informasi dalam penelitian ini, menggunakan berbagai sumber, media online ataupun media cetak. Seperti buku, artikel ilmiah, yang ada di nasional ataupun internasional yang berkaitan dengan fungsi kepemimpinan dalam meningkatkan mutu pembelajaran di sekolah dasar. Hasil dari evaluasi yang dilakukan menunjukkan bahwa fungsi kepemimpinan sangat menentukan mutu pembelajaran di sekolah dasar. Guru sebagai kepemimpinan di dalam kelas juga sangat menentukan mutu pembelajaran. Sehingga peneliti dapat menyarankan, jika ingin meningkatkan mutu pembelajaran di sekolah dasar, maka tingkatkan evaluasi terhadap fungsi kepemimpinan di sekolah dasar di Bengkulu.Kata Kunci : Evaluasi, Fungsi kepemimpinan, Mutu Pembelajaran, Sekolah Dasar